Trematocine, a Novel Antimicrobial Peptide from the Antarctic Fish Trematomus bernacchii: Identification and Biological Activity - Giulia Della Pelle; Giulia Perà; Maria Cristina Belardinelli; Marco Gerdol; Martina Felli; Silvia Crognale; Giuseppe Scapigliati; Francesca Ceccacci; Francesco Buonocore; Fernando Porcelli (Antibiotics, 2020)
Antimicrobial peptides (AMPs) are short peptides active against a wide range of pathogens and, therefore, they are considered a useful alternative to conventional antibiotics. We have identified a new AMP in a transcriptome derived from the Antarctic fish Trematomus bernacchii. This peptide, named Trematocine, has been investigated for its expression both at the basal level and after in vivo immunization with an endemic Antarctic bacterium (Psychrobacter sp. TAD1). Results agree with the expected behavior of a fish innate immune component, therefore we decided to synthesize the putative mature sequence of Trematocine to determine the structure, the interaction with biological membranes, and the biological activity. We showed that Trematocine folds into a α-helical structure in the presence of both zwitterionic and anionic charged vesicles. We demonstrated that Trematocine has a highly specific interaction with anionic charged vesicles and that it can kill Gram-negative bacteria, possibly via a carpet like mechanism. Moreover, Trematocine showed minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values against selected Gram-positive and Gram-negative bacteria similar to other AMPs isolated from Antarctic fishes. The peptide is a possible candidate for a new drug as it does not show any haemolytic or cytotoxic activity against mammalian cells at the concentration needed to kill the tested bacteria.